As minorias Sociais nos Espaços de Constituência do Teológico no Gênero de Discurso Parábola - Junior, Candido Ferreira de Souza (2020)
Our research has as its theme the study of social minorities in the functioning of theological discourse, in the parable genre, based on the theoretical-methodological apparatus of French Discourse Analysis (DA), according to the enunciative-discursive pe